(untitled) (Research, Society and Development, 2022)
Nursing professionals have encountered many adversities in promoting care for autistic children and adolescents. This study aims to understand the challenges and potential of nursing in the care of autistic children and adolescents and the difficulties faced by these patients in terms of health care, based on the nursing team in the public health context. This is an integrative literature review, with a qualitative approach, with the purpose of verifying the types of care, in the different spectrums that the disorder presents and the rights of these individuals, according to the laws. unusual behaviors, such as not liking to interact, being agitated or repeating movements, behaviors found mainly in the results showed that children with ASD have language and communication disorders, difficulty in social interaction and attachment to fixed routines and repetitive and stereotyped behaviors, and for reasons like this, the nurse has a fundamental role in this scenario, since this professional is the gateway to the entire hospital environment, so it is essential that they are professionals trained to perform nursing care for these patients and their entire family. It is important to note that, in order to have qualified professionals, it is also necessary for public health, the Unified Health System (SUS), to be open to these children and adolescents with an entire team available.